Mobility Optimization in LTE Heterogeneous Network - Guoping Chen; Qingbo Du (Dianxin kexue)
The long term evolution （LTE）network is an advanced mobile network defined in 3GPP. The node density of LTE network is higher than traditional 2G and 3G mobile networks, because not only the inter-sector distance is smaller, but also more and more small cells are integrated into the network. The mobility management has become a challenge in a dense heterogeneous network. An advanced handover mechanism to solve the high handover failure rate problem in LTE heterogeneous network（HetNet）was proposed. Simulation results show that the proposed mechanism increases the handover performance in HetNet.